Bimbingan Dan Layanan Terapi Pada Anak Autis - Frendi Fernando (QALAM: JURNAL PENDIDIKAN ISLAM, 2021)
Autistic disorder is the presence of developmental disorders or abnormalities in social interaction and communication and is characterized by limited activity and interest. The appearance of this disorder largely depends on the stage of development and chronological age of the individual. Children with autism is one of the developmental disorders of pervasive brain function that includes cognitive impairment, language, behavior, communication, and social interaction disorders, so that it has its own world. The main goal in tackling autism is to reduce the symptoms associated with autism and reduce the pressure that occurs in the family. Children with autism can be trained through therapy in accordance with the condition and needs of children, among others through speech therapy, occupational therapy, play therapy, medical therapy / drugs ( drugs ), sensory integration therapy, auditory integration therapy, biomedical treatment / therapy, hydro therapy and music therapy. Education services for autistic children are also very diverse such as transition classes, inclusion education programs, integrated education programs, home school programs, autistic rehabilitation centers. This form of service aims to make the autistic child more independent and develop the potential that exists in him.